THE CARIES MANAGEMENT SYSTEM: UPDATING COST-EFFECTIVENESS WITH 4-YEAR POSTTRIAL DATA. (15th August 2016) - Warren, Emma; Curtis, Bradley H.; Jia, Nan; Evans, R. Wendell
Abstract : Objectives: Long-term follow-up of the Caries Management System (CMS) protocol demonstrated that regular monitoring and noninvasive management of dental caries is effective in reducing the number of caries-related events over a 7-year period. This analysis complements the authors' original economic evaluation of the CMS by re-evaluating the per-protocol cost-effectiveness of the CMS approach. Methods: An individual patient-simulation Markov model was developed previously, based on 3-year randomized-controlled trial (RCT) data, to simulate the incidence and progression of dental caries, and resultant interventions, and to evaluate the lifetime cost-effectiveness of the CMS versus standard dental care from the Australian private dental practitioner perspective (in which the baseline age distribution was similar to that of the Australian population). The 4-year posttrial follow-up data are used to re-evaluate the long-term cost-effectiveness of the CMS in a more real-life setting. Results: The reduction in caries risk was maintained among those practices within which the CMS protocols were adhered to. The per-protocol model appears to be reasonably accurate at predicting the risk of restorative events in the posttrial follow-up period. The per-protocol lifetime cost per restorative event avoided is AUD1, 980 (USD1, 409; 1 AUD = 0.71 USD). Conclusions: The current analysis confirms that the CMS approach is both effective, when the protocols are adhered to appropriately, and cost-effective compared with standard care in the Australian private practice setting.